Analysis of Mathematical Representation Skills in the Topic of Probability Reviewed from the Read or Write Learning Style - R, Fatkhunur Fariza; Sujadi, Imam; Pramudya, Ikrar (KnE Social Sciences, 2025)
This study describes mathematical representation on students’ read/write learning style in solving probability problems. It uses qualitative research to study the students of class VIII A of SMPN 3 Ngawi. The research data is based on the results of learning style tests given to students and mathematical representation tests. Subjects with a read/write learning style were given a mathematical representation test followed by an interview test. They were found to have symbolic representation ability which is conducive to understanding the given problems, having good visual representation skills in understanding the problem of opportunity events, good image representation skills in understanding the given problems.